Reagent combinations in flocculation - C. Rattanakawin (2018)
The use of various reagents, separately and in combination, for the flocculation of fine-particle dispersions has been investigated using a light-scattering technique to determine floc size distributions. The results demonstrate that the process involves two distinct phases: particle destabilization and floc growth, each with its own reagent requirements. Destabilization can be achieved by electrical double-layer suppression through the addition of simple electrolytes or by pH control. Low molecular weight but highly active polymers can also be used for this purpose. The addition of high molecular weight polymers to stable dispersions can cause some flocculation by the bridging process, but unless excessive quantities are used they tend to leave behind a significant amount of dispersed primary particles leading to high supernatant turbidity. On the other hand, such polymers are shown to be very effective in promoting the growth of flocs to large sizes in previously destabilized systems. The experiments also demonstrate the importance of the order of reagent addition. Reversing the order - adding the destabilizing agents after treatment with a high molecular weight polymer - is shown to be quite ineffective. Copyright 2005, Society for Mining, Metallurgy, and Exploration, Inc.